The bluetooth and GPS tracking system: Comparison and analysis of technique - Idris, Ariff; Ismail, Mahamod; Nordin, Rosdiadee; Hamdan, Muhammad Hasif; Abdul Hamid, Mohd Hakim; Salahuddin, Lizawati; Baharon, Mohd Rizuan; Abdullah, Nurlisa Loke; Hasan Basari, Abd Samad; Raja Ikram, Raja Rina (Science and Engineering Research Support Society, 2019)
In recent years, tracking system is a popular approach to detect misplaced objects due to the availability of related systems in the market. The common technologies used are RIFD, Bluetooth, WIFI and GPS. Following framework more often than not consolidates the utilization of an electronic gadget (equipment) with portable application (programming) that tracks the missing objects. Numerous structures likewise join verbal trade parts together with satellite TV for pc transmitters to communicatewith equipment's for a distant client. Google maps are utilized to observe the equipment's region. This examination is centered around two administrations in following lost question. The first one is GPS and the second one is Bluetooth. The ascent of Bluetooth Low Energy (known as BLE or Bluetooth 4.0) opens up to unlimited potential outcomes of Bluetooth following applications. On the other hand, GPS is a service that communicates with satellites, provides location on the globe, and gives coordinates of the location tracker.